Odpowiedzi

2010-02-17T16:18:37+01:00
Zamień sumę na iloczyn.
a) 3a - 3
3 * (a-1)

b) 4 + 4x
4 * (1 + x)

c) 6m - 6a
6 * (m - a)

d) 8a - 16
8 * (a - 2)

e) 15b + 10
5 * (3b + 2)

f) 16b - 12c
4 * (4b - 3c)

g) 12x + 36y
12 * (x + 3y)

h) y - 3y
y * (1 - 3)

i) 15a² + 12b²
3 * (5a² + 4b²)

j) 24x² - 16y
4 * (6x² - 4y)

k) 12a² - 8b
4 * (3a² - 2b)

l) 10n - 15m
5 * (2n - 3m)
Najlepsza Odpowiedź!
2010-02-17T16:20:17+01:00
A) 3a - 3=3(a-1)
b) 4 + 4x=4(1+x)
c) 6m - 6a=6(m-a)
d) 8a - 16=8(a-2)
e) 15b + 10=5(3b+2)
f) 16b - 12c=4(4b-3c)
g) 12x + 36y=12(x+3y)
h) y - 3y=-2y
i) 15a² + 12b²=3(5a² + 4b²)
j) 24x² - 16y=8(3x² - 2y)
k) 12a² - 8b=4(3a² - 2b)
l) 10n - 15m=5(2n-3m)
2010-02-17T16:24:07+01:00
A) 3a - 3=3(a-1)
b) 4 + 4x=4(1+x)
c) 6m - 6a=6(m-a)
d) 8a - 16=8(a-2)
e) 15b + 10=5(3b+2)
f) 16b - 12c=4(4b-3c)
g) 12x + 36y=12(x+3y)
h) y - 3y=y(1-3)
i) 15a² + 12b²=3(5a²+4b²)
j) 24x² - 16y=8(3x²-2y)
k) 12a² - 8b=4(3a²-2b)
l) 10n - 15m=5(2n-3m)